Development of a separation framework for effects-based targeted and non-targeted toxicological screening of water and wastewater. (1st March 2020) - Pochiraju, Susheera S.; Linden, Karl; Gu, April Z.; Rosenblum, James
Abstract: An environmental water sample fractionation framework was developed based on effects-directed analysis (EDA) to detect known and unknown compounds of concern in different waters. Secondary effluent from a wastewater treatment plant was used to demonstrate the effectiveness of the developed framework for characterizing estrogenic compounds in the effluent. The effluent was spiked with known estrogenic compounds to validate the framework in a targeted approach and an unspiked sample was also investigated in a non-targeted approach. The framework separated compounds based on polarity and adsorption using liquid-liquid extraction followed by solid phase extraction. The targeted and non-targeted effluents generated six fractions each, which were assessed for estrogenic activity using an in vitro bioassay (yeast estrogen screen - YES). Three out of the six fractions in each case, along with the raw effluent, showed estrogen equivalent concentrations (EEQs) ranging between 1.0 and 3.0 μg/L. Directed by the assay results, these estrogenic fractions were further analyzed using liquid- and gas-chromatography coupled with mass spectrometry for compound identification. The developed separation framework coupled with a bioassay aided in identification of both known and unknown compounds producing estrogenic effects in the water sample. The approach of fractionation followed by concentration helped isolate and elevate contaminant levels without necessarily concentrating potential matrix effects that could cause interfering cytotoxicity and inhibition in the bioassay. The targeted analysis showed consistency between predicted and observed results, while the non-targeted analysis revealed the presence of three estrogenic compounds in the unspiked effluent: di-isobutyl phthalate, diethyl phthalate and benzophenone, that were confirmed with standards. The study mainly aimed at development and validation of a simple yet effective EDA framework with low cost techniques for water and wastewater toxicity screening and evaluation, and the results suggested that the developed framework could be used as a screening tool for isolating and identifying unknown compounds in a complex water sample. Graphical abstract: Image 1 Highlights: EDA-based separation framework to detect toxic compounds in wastewater. Bioassay combined with LC- and GC-MS for targeted and non-targeted EDA analyses. Yeast estrogen screen used to confirm the estrogenicity of the detected compounds. EDA framework resulted in three identified estrogenic compounds in the wastewater. Estrogenic contributions of the compounds to the wastewater were quantified.